Autism Case Report: Cause and Treatment of “High Opioid Tone” Autism - Anugu, Vishal; Ringhisen, John; Johnson, Brian (Frontiers in Psychology, 2021)
Introduction: Neurobiological systems engineering models are useful for treating patients. We show a model of “high opioid tone” autism and present a hypothesis about how autism is caused by administration of opioids during childbirth. Main Symptoms: Clinical diagnosis of autism in a 25 year old man was confirmed by a Social Responsiveness Scale (SRS) self - rating of 79, severe, and a Social Communications Questionnaire (SCQ – 2) by the patient’s father scoring 27. Cold pressor time (CPT) was 190 seconds – unusually long, consonant with the high pain tolerance of autism. Therapeutic Intervention and Outcomes: At naltrexone 50 mg/day SRS fell to 54 and SCQ – 2 to 9; both non – significant. CPT fell to 28, repeat 39 seconds. Improved relatedness was experienced ambivalently, understood as feelings never before experienced - causing pain. Non – compliance with naltrexone was followed by cutting open his palm and drinking alcoholically. Transference focused psychotherapy has helped him remain naltrexone - compliant while he works on issues of identity and relatedness. Conclusion: The model suggests studies that could be conducted to both prevent and treat this form of autism.